2017
DOI: 10.5455/ijmsph.2017.1060318112016
|View full text |Cite
|
Sign up to set email alerts
|

A community-based study on prevalence of hypertension in urban Shimoga, Karnataka

Abstract: It is the most common cardiovascular disorder, posing a major public health problem of the world and especially to the population in socioeconomic and epidemiological transition. [1] It is one of the major and independent risk factors for non-communicable diseases (NCD) such as cerebrovascular disease, coronary heart disease, and cardiac and renal failure. [2] The recent WHO report states that considering the prevalence of any diseases, hypertension ranks fourth in the world. [3] As it is hidden beneath an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
2
2
1
Order By: Relevance
“…A significant sex differences in mean blood pressure was observed in the present study with men showing higher increase in blood pressure than women both in rural and urban areas. Consistent with the present findings, studies on other Indian population also shows sex variation in blood pressure reporting males with higher values of blood pressure than their female counterparts (Ghosh et al, 2016;Gopalakrishnan et al, 2017;Nagendra et al, 2017;Nirmala, 2001;Sidhu & Prabhjot, 2007;Simon et al, 2017). According to Reckelhoff (2001), although the causes of sex differences in blood pressure are not clear, there is certain evidence that androgens, such as testosterone, could play an important role in regulating the sex differences in blood pressure.…”
Section: Discussionsupporting
confidence: 89%
“…A significant sex differences in mean blood pressure was observed in the present study with men showing higher increase in blood pressure than women both in rural and urban areas. Consistent with the present findings, studies on other Indian population also shows sex variation in blood pressure reporting males with higher values of blood pressure than their female counterparts (Ghosh et al, 2016;Gopalakrishnan et al, 2017;Nagendra et al, 2017;Nirmala, 2001;Sidhu & Prabhjot, 2007;Simon et al, 2017). According to Reckelhoff (2001), although the causes of sex differences in blood pressure are not clear, there is certain evidence that androgens, such as testosterone, could play an important role in regulating the sex differences in blood pressure.…”
Section: Discussionsupporting
confidence: 89%
“…More specifically, females have shown greater vulnerability to develop obesity and central adiposity. Males, on the other hand, were found to be more susceptible to hypertension, which was also reported in earlier studies (Ghosh et al, 2016; Gopalakrishnan et al, 2017; Lalnuneng, 2022; Nagendra et al, 2017; Simon et al, 2017). However, data collected on tribal populations from different regions of India, reported inconsistent results of higher prevalence of hypertension in females (14.0%) than in their counterpart males (9.2%, Kshatriya & Acharya, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…38 The results of the current study are in accordance with the study found that hypertension was more prevalent in males and the prevalence of hypertension increased with age and declined only in the 55-64 years age group. 25 On contrast to the current study, it was reported that physical activity is not a predictors for the occurrence of hypertension in Indian rural areas. 39…”
Section: Discussioncontrasting
confidence: 95%
“…24 On the other hand, It was found that the prevalence of hypertension in urban India 26.5%. 25 Moreover, a study in Iran 26 stated a prevalence rate of hypertension of 20.1%; of whom self-reported hypertension was 12.3%. This discrepancy in the prevalence rates may be attributed to variation in the sociodemographic characteristics, especially age distribution and residence (urban versus rural) and due to sampling variability.…”
Section: Discussionmentioning
confidence: 99%